Plaidoirie pour pratiquer la recherche autrement. La transition juste en Asie du Sud-Est - Benjamin Buclet; Stéphane Lagrée (VertigO)
The report released in early 2022 by UNESCO’s Global Independent Expert Panel on Universities and the 2030 Agenda (EGU2030, 2022) alerts to the need for a deep transformation of the higher education sector in the service of global sustainability. The second part of the IPCC's Sixth Assessment Report on climate change, published on February 28th, reveals the extent of a threat that has significantly worsened. In response to the findings and recommendations, an Alliance of Southeast Asian Universities, from the Mekong countries, will commit to a strategy of openness to the extra-academic world, for knowledge-based actions and solutions for and with all stakeholders.In this region, environmental degradation and uncertainties about future growth prospects require a rethinking of development strategies. To this end, higher education and research institutions must contribute to build the next generation of policy makers for environmental transition and set up a network of experts in sustainability science. It is through the prism of such a paradigm shift for a just transition that knowledge will be able to inform the dialogue on the public policies to be implemented.The operating method proposed by the authors of this article is based on four complementary levers - the production of a critical mass of knowledge, communication, scientific dissemination connected to local societies, and an intensification of capacity building - for the study of environmental transition and inequalities in Cambodia, Laos, Myanmar, Thailand and Vietnam.